Métodos multivariados no estudo da diversidade genética e adaptabilidade e estabilidade em soja convencional - Felici, Paulo Henrique Nardon (2017)
The study of genetic diversity and the knowledge of the relationships among improved cultivars are fundamental for soybean breeding programs, since they help the selection of breeders and recommendation of cultivars. This thesis is subdivided into three chapters, the first one deals with a theoretical reference regarding the culture, the economic importance and the improvement of soybean. The second chapter was developed with the objective of evaluating the genetic diversity from phenotypic traits, of conventional early maturity soybean genotypes in different environments, determining the importance of traits in soybean genetic divergence and selecting parents of broad genetic diversity for breeding programs, using different multivariate clustering methods. The experiment was conducted in two distinct locations, Campo Novo dos Parecis - MT, season 2010/2011 and Urutaí - GO, season 2012/2013. Ten genotypes of conventional early maturity soybean were evaluated in a randomized complete block design, in which eight agronomic characters were measured. By univariate and multivariate analyzes it was possible to conclude that the groupings formed by all the multivariate methods, with the means of the phenotypic values of the genotypes, allowed to infer about the promising combinations for artificial hybridizations. Number of days for flowering, plant height at maturity and height of insertion of the first pod were the characters that contributed the most to the genetic divergence in soybean when considering the two crop environments. UFU 106 and UFU 108 lines are the most recommended as part of the hybridizations with divergent genotypes, since they are complementary in grain yield and lower vegetative phase. Hybridizations between the following pairs of genotypes are recommended to obtain segregating populations with superior genetic variability: UFU 106 x UFU 112; UFU 106 x Emgopa 316; UFU 108 x Emgopa 316; UFU 112 x Emgopa 316. The third chapter was elaborated to evaluate the genotype interaction by environments for grain yield characteristics in conventional soybean genotypes of early maturity, grown in 15 environments distributed in five Brazilian states, to determine the adaptability and stability of the genotypes by parametric, non-parametric and multivariate methods. Wricke (1965), Eberhart and Russel (1966) and AMMI methods identified UFU 21 and UFU 22 lines as the most stable, both with grain yields higher than 3800,00 kg ha-1. The strain UFU 06 obtained an average grain yield of more than 4000,00 kg ha-1 and presented wide adaptation by Annicchiarico (1992), Lin and Binns (1988) modified by Carneiro (1998) and Centroid methods.